1977
DOI: 10.1080/00288306.1977.10420698
|View full text |Cite
|
Sign up to set email alerts
|

Dating of geochemical events in Lake Bonney, Antarctica, and their relation to glacial and climate changes

Abstract: Measurements of major ion concentrations, 1) 18 0 , and 14C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 20 publications
1
62
0
Order By: Relevance
“…One or more of these processes may account for the distribution of dissolved solutes in icecovered coastal ponds (Matsubaya et al 1979;Bird et al 199 1) and in several dry valley lakes in the McMurdo Sound region of southern Victoria Land. Distinguishing between these processes is critical to understanding regional paleoclimate because the evaporative concentration hypothesis has been used to estimate the timing of desiccation in several McMurdo Dry Valley lakes (Wilson 1964;Hendy et al 1977;Lawrence 1982;Lawrence and Hendy 1985; W. B. Lyons pers. comm.)…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…One or more of these processes may account for the distribution of dissolved solutes in icecovered coastal ponds (Matsubaya et al 1979;Bird et al 199 1) and in several dry valley lakes in the McMurdo Sound region of southern Victoria Land. Distinguishing between these processes is critical to understanding regional paleoclimate because the evaporative concentration hypothesis has been used to estimate the timing of desiccation in several McMurdo Dry Valley lakes (Wilson 1964;Hendy et al 1977;Lawrence 1982;Lawrence and Hendy 1985; W. B. Lyons pers. comm.)…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Attempts to explain the origin of saline bottom water in closed-basin, antarctic lakes have focused on relict seawater (Hendy et al 1977;Masuda et al 1988) evaporative concentration of a pre-existing water body (Lawrence and Hendy 1985;Torii et al 1989), and input of high-salinity groundwaters or modified surface waters (Green and Canfield 1984;Green et al 1989). One or more of these processes may account for the distribution of dissolved solutes in icecovered coastal ponds (Matsubaya et al 1979;Bird et al 199 1) and in several dry valley lakes in the McMurdo Sound region of southern Victoria Land.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated salts are postulated to have been ablated (Lyons et al 1992). In contrast, Lake Fryxell did not completely dry out, but remained a saline pond (Hendy et al 1977;Lawrence and Hendy 1985;Lyons et al 1992). Green et al (1988) suggested that the chloride age of Lake Hoare is younger (2,200 years) than Lake Fryxell (3,000 years).…”
Section: Mechanisms For Convectionmentioning
confidence: 99%
“…Armed with this hypothesis, the solute profiles from Lakes Vanda (in Wright Valley) and Fryxell (in Taylor Valley) have been used by Hendy et al (1977). the atmosphere).…”
mentioning
confidence: 99%